Husserl and Weyl - Da Silva, Jairo Jose [UNESP]; Centrone, S. (Springer, 2017)
In this paper, I carry out a comparative study of the philosophical views of Edmund Husserl and Hermann Weyl on issues such as mathematical existence and mathematical intuition, the validity of classical logic, the concept of logical definiteness, the nature of symbolic mathematics, the role of mathematics in empirical science, the relation of scientific theories with perception, space representation and the philosophy of geometry, and intentional constitution in general. My main goal is not simply to assess the extent of Husserl's influence on Weyl, although this is an ever present concern, but to clarify the views of one by contrasting them with those of the other.
Keywords: Weyl; Philosophy of mathematics; Philosophy of logic; Philosophy of science